Neutrophil response and function during acute cytomegalovirus infection in guinea pigs. - Yourtee, E L (1982)
The mobilization and functional characteristics of polymorphonuclear leukocytes (PMNs) at the site of an inflammatory stimulus were studied during acute cytomegalovirus infection in guinea pigs. Weanling Hartley strain guinea pigs were inoculated subcutaneously with approximately 10(6) 50% tissue culture infective doses of virulent salivary gland-passaged guinea pig cytomegalovirus. The virus was uniformly present in bone marrow, buffy coat, and casein-elicited peritoneal exudate cells 5 to 7 days after the inoculation. The mean numbers of circulating PMNs in the animals were 2,862/microliters in uninfected controls and 880/microliters in infected animals. The total peritoneal PMNs recovered 14 h after casein injection were 491 X 10(6) and 237 X 10(6) in control and infected animals, respectively. The number of 50% tissue culture infective doses of guinea pig cytomegalovirus per 10(6) purified peritoneal PMNs was 10(2.17). Neutrophil O2 consumption was similar in infected and control animals in response to either stimulation by a neutrophil activator, phorbol myristate acetate, or phagocytosis of Staphylococcus aureus. However, the maximal rate of H2O2 release and the percent killing of S. aureus by peritoneal exudate cells from infected animals were significantly reduced compared with uninfected controls during acute infection. Granulocytopenia, a decreased mobilization of PMNs to the site of the inflammatory stimulus, a diminished cellular release of H2O2 in response to a bacterial stimulus, and a modest reduction in bacterial killing were demonstrated during experimental acute cytomegalovirus infection. Such reductions in granulocyte number and function at inflammatory sites during this type of infection could alter antimicrobial defenses.